Pemetaan Tata Kelola Interaktif Jasa Provisioning Ekosistem Skala Kecil: Pendekatan Sistem Sosial-Ekologi Di Teluk Jor, Lombok Timur - Wahid, Mathori Abdul; Adrianto, Luky; Zairion, Zairion; Adhuri, Dedi Supriadi (Universitas Diponegoro, 2025)
The utilization of coastal and marine resources in Teluk Jor, East Lombok, faces significant pressures that threaten the sustainability of small-scale ecosystem provisioning services, such as mangroves, seagrass beds, and coral reefs. This study aims to map the social-ecological system (SES) network using the Social-Ecological Network Analysis (SENA) approach based on the Russian Doll Framework. Primary data were obtained through field observations and in-depth interviews with 68 respondents, including fishers, community leaders, fisheries extension officers, and relevant institutions. Secondary data were collected from previous literature reviews. The analysis results indicate that the Local Rule (customary regulations) holds the highest degree centrality (10), followed by ResThreat (ecosystem threats) such as mangrove conversion and destructive fishing practices (9), and HumConFac (human-made infrastructures) including floating net cages, salt ponds, and shrimp ponds (8). Regarding betweenness centrality, the Local Rule occupies the most central position (59.67), followed by HumConFac (49.83), ResThreat (32.67), and EcoQual (ecosystem quality) (24.50). These findings demonstrate that customary institutions play a crucial role in connecting governance actors, while economic activities and ecological threats significantly shape SES network dynamics. This study underscores the need for adaptive governance strategies that integrate collaboration among communities, government, and stakeholders to ensure ecosystem sustainability while supporting the well-being of coastal communities. Pemanfaatan sumber daya pesisir dan laut di Teluk Jor, Lombok Timur, menghadapi tekanan signifikan yang mengancam keberlanjutan jasa provisioning ekosistem skala kecil, seperti mangrove, lamun, dan terumbu karang. Penelitian ini bertujuan untuk memetakan jejaring social-ecological system (SES) menggunakan pendekatan social-ecological network analysis (SENA) berbasis Russian Doll Framework. Data primer diperoleh melalui observasi lapangan dan wawancara mendalam dengan 68 responden, mencakup nelayan, tokoh masyarakat, penyuluh perikanan, serta instansi terkait. Data sekunder dikumpulkan dari kajian literatur sebelumnya. Hasil analisis menunjukkan bahwa Local Rule (aturan lokal) memiliki nilai degree centrality tertinggi (10), diikuti oleh ResThreat (ancaman ekosistem) seperti konversi mangrove dan praktik perikanan destruktif (9), serta HumConFac (infrastruktur buatan) seperti KJA, tambak garam, dan tambak udang (8). Pada indikator betweenness centrality, Local Rule menempati posisi sentral (59,67), diikuti HumConFac (49,83), ResThreat (32,67), dan EcoQual (kualitas ekosistem) (24,50). Temuan ini menunjukkan bahwa kelembagaan adat memainkan peran penting dalam menghubungkan aktor-aktor tata kelola, sementara aktivitas ekonomi dan ancaman ekologis berperan besar dalam membentuk dinamika jaringan SES. Penelitian ini menegaskan perlunya strategi tata kelola adaptif yang mengintegrasikan kolaborasi antara masyarakat, pemerintah, dan pemangku kepentingan, guna menjaga keberlanjutan ekosistem sekaligus mendukung kesejahteraan masyarakat pesisir.